5-Azacitidine and Trichostatin A induce DNA damage and apoptotic responses in tongue squamous cell carcinoma: An in vitro study. (January 2022) - Hodjat, Mahshid; Jourshari, Parisa Bina; Amirinia, Fatemeh; Asadi, Nasrin
Abstract: Objective: The present in vitro study aims to investigate the potential use of epigenetic inhibitors as treatment modalities in tongue squamous cell carcinoma. Design: The human tongue squamous cell carcinoma cell line (CAL-27) was cultured and exposed to varying concentrations of 5-Azacitidine (5-Aza) or Trichostatin A (TSA) in the culture medium. The cell apoptosis was evaluated using Annexin V/PI by flow cytometry. To evaluate DNA damage response, γH2AX foci analysis was performed using immunofluorescence. Single cell gel electrophoresis (SCGE) was applied to measure DNA strand breaks. Gene expression was assessed by quantitative real-time PCR. Results: The results showed that 5-Aza and TSA had apoptotic effects on the SCC cell line at concentrations of 50–200 µM and 0.5–5 µM, respectively. Immunofluorescence analysis showed increased expression of γH2AX, the marker of DNA damage response after treatment of 5-Aza and TSA that was associated with increased DNA strand breaks. The expressions of urokinase plasminogen activator, its receptor and matrix metalloproteinase-2, were significantly reduced in TSA- and 5-Aza-treated cells. Conclusions: Our results showed that 5-Aza and TSA increase apoptotic and DNA damage response in squamous cell carcinoma cell line while reducing the expression of tumor invasion genes that further indicating the potential therapeutic value of two epigenetic modifiers in squamous cell carcinoma. Graphical Abstract: ga1 Highlights: 5-Azacitidine and Trichostatin A cause DNA strand breaks in squamous cell carcinoma cell line. 5-Azacitidine and Trichostatin A induce phosphorylation of histone H2AX. 5-Azacitidine and Trichostatin A reduce the expression of tumor invasion genes. The expression of urokinase plasminogen activator is affected by epigenetic modulators. The expression of matrix metallopeptidase 2 is affected by epigenetic modulators.